How Sleep Impacts Performance in Youth Athletes. Issue 11 (November 2020) - Riederer, Mark F.
Abstract : Abstract: Sleep is an important aspect in the recovery and performance in athletes. Recently, there has been increasing interest in exploring the various affects that sleep has on performance in athletes. Youth athletes represent a unique population in that not only do they have demands in training schedules and training load, but they also have demands in academics. There is a growing body of evidence to suggest that youth athletes do not get the recommended required amount of sleep and that this has negatively affected performance and well-being. The focus of this article is to review the most recent literature over the past year that investigates the impact of sleep on youth performance.